FAKTOR-FAKTOR PERNIKAHAN PAKSA (NIKAH SIRRI) DI DESA SIMPANG KANAN KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Ubaidillah, Ubaidillah; Marluwi, Marluwi; Muzammil, Sa’dulloh (Al-Usroh, 2022)
The purpose of this study was to find out: 1) What factors caused forced marriages to be carried out in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency; 2) In order to find out the opinion of religious leaders regarding forced marriages in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency. This research uses qualitative research which is classified into field research and normative-empirical approach. The data sources in this study used primary data sources in the form of interviews with religious leaders in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency, whose subjects had been determined, while secondary data sources were books, laws, regulations, journals, and works. other scientific sources that can complement and strengthen this research. The data collection technique in this study was using interviews. Furthermore, the data analysis technique, the researcher uses data reduction, data presentation, and drawing conclusions. The technique for checking the validity of the data is using a member check. The results obtained in this study indicate that: 1) The factors of forced marriage in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency, some people who carry out forced marriages are carried out due to several factors as follows: Social norms factors, Parents factors , the kiai/teacher factor; 2) Forced marriage according to religious leaders in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency, a. Forced marriage is considered normal by some people, b. Based on the opinion of religious leaders who refer to the opinion of Imam Syafi'i that forced marriages may be carried out, c. Marriages carried out by force in Simpang Kanan Village, Sungai Ambawang District, Kubu Raya Regency are still allowed according to the opinions expressed by religious leaders. Keywords: Marriage, Forced Marriage, Religious Leader